mu-Acetato-bis(mu-2-{[(3-chloro-2-hydroxypropyl)(2-pyridylmethyl)amin o]methyl}phenolato)dinickel(II) chloride - Tiekink, E.R.T.; Wardell, J.L.; Fernandes, C.; Horn, A.; Skakle, J.M.S. (International Union of Crystallography, 2010)
The title salt, [Ni(2)(C(16)H(18)ClN(2)O(2))(2)(CH(3)COO)]Cl, features a dinuclear cation in which the Ni atoms are triply bridged by two phenolate O ligands and a bidentate acetate ligand with all of the bridging distances essentially symmetric. Each Ni atom is also coordinated by the amine N, pyridine N and hydroxy O atoms of the 2-{[(3-chloro-2-hydroxypropyl)(2-pyridylmethyl) amino]methyl} phenolate ligand which is, therefore, pentadentate. The resultant N(3)O(3) donor sets define octahedral coordination geometries. The chloride counter-anion is connected to the cation via two Ohydroxy-H center dot center dot center dot Cl hydrogen bonds.